CRACKERS TINGGI SERAT DARI FORMULASI TEPUNG JAMBU BIJl - Sri Budi Wahjuningsih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2004)
Dietary fiber have positively effect on the nutrition and metabolism of human body. Guava can be used as source of fiber and contain dietary fiber highest among the fruits (5,6g/100g). The aim of this research was studying the use of guava flour as the source of fiber on crackesr in order to develop the kinds of healthy food products.The experiment design was used com pletely randomized design in four replicate,continued with Honestly Significant Different at 5 % level. The treatment is the substitution of guava flour 0%, 5%, 10%, 15%, and 20%. In this experiment; test were caried out to determine proximate analysis, dietary fiber analysis, texture and sensory atributtes which include colour, aroma and general acceptance.The result of the research showed that substitution of guava flour had significant effect on fat and dietary fiber content ; color and general acceptance. Cracker prepared by substitution of guava flour until I 0% was preferred by the panels and they provided water content 3,974%, mineral content 1,5427%, fat content 3,1333%, carbohydrate content 80,918%, protein content 10,4296% and dietary fiber content 7,2599%. Preparation to improve guava flour color and the use of agent to improve the sensory properties of the crackers are necessary